View of Mazagon Dock from Gaondevi Temple - Mumbai Archive Project Team (Jio Institute, 2024)
View of Mazagon Dock from Gaondevi Temple on Mazagon Hill. Established in 1774 by the Wadia family of shipbuilders, the Mazagon Docks are primarily used for the construction of warships and submarines for the Indian Navy. This includes maintenance, upgrades, and modernization of ships and submarines to extend their operational lives. In addition, the docks are also used for the repair and refitting of old naval vessels.